Zinc-aluminum-magnesium coated steels, a microelectrochemical investigation of the corrosion processes arising at the cut edges - Bolsanello, Marilia Fernandes (2024)
Advanced coatings tailored to enhance the corrosion protection of steels are the target of the automotive industry, as they ensure the reliability and long-term performance of coated parts. In this study, microelectrochemistry supports the understanding of the corrosive process that occurs with a steel metallic coated with Zn-3.5%Al-3%Mg (% mass) when subjected to aggressive aqueous electrolytes, with emphasis on acid rain of the city of São Paulo. Though, samples of the material with different coating thickness were analyzed by scanning electrochemical microscopy (SECM) and scanning vibrating electrode technique (SVET), focusing on the cross sections of coated steels. An electrochemical cell fixture was developed, in which the samples were inserted in the vertical position, exposing both the cross-section and the metal surfaces to the electrolyte, and enabling spatially resolved measurements at the cut edges. This allowed SECM local analysis of hydrogen evolution and oxygen consumption. In SVET, changes in the probe angle, as well as the use of the new cell, allowed for continuous monitoring of the ionic currents in the cross-section and on both galvanized steel faces. Scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDS) and glow-discharge optical emission spectroscopy (GDOES) were auxiliaries in mapping structures, identifying elements and compounds in the Zn-Al-Mg coating layer. This range of tests allowed verifying the coating\'s action in real time, when subjected to acid rain reproduced in the laboratory. By the SECM maps we noticed the intensification of the cathodic activities in the substrate region as well as an attenuation of the local pH. By SVET, the cross-section protection was reconfirmed, and high cathodic activity was detected at the midpoint of the steel specimen. The neutralization of anodic spots was attributed to the formation of stable corrosion products based on zinc, aluminum and magnesium. The stability of the coating was demonstrated to predominantly hinge upon the uniformity and aspect of the coated surface, rather than its thickness.